Psychosocial impact of career-ending injuries in professional ice hockey players : a qualitative study - Nässi, Anu (2014)
Injuries are a regular occurrence amongst athletes, and on occasion so severe as to impact the continuation an athlete’s career. Retirement from sport, in any circumstances can be a difficult transition for an athlete, particularly when participation in sport has formed a significant part of their identity, personality, and life as a whole. Research in this area is limited, as existing studies focus on injury and career termination separately. Thus, the purpose of this study was to document the lived experiences of professional ice hockey players who have encountered career-ending sports injuries. Three former professional Finnish ice hockey players participated in this study, all of who had played in Finland’s top ice hockey league (Liiga). Data were collected through individual, semi-structured interviews. Following prolonged engagement and transcription, the data were analysed in accordance to guidelines for interpretative phenomenological analysis.